2016
DOI: 10.1002/bsl.2251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Health and Neuroscience Evidence on Juror Perceptions of a Criminal Defendant: the Moderating Role of Political Orientation

Abstract: Several recent studies have examined the effects of mental health and neuroscientific evidence on attitudes toward criminal defendants, suggesting that these factors may influence juror decision-making in meaningful ways. Few studies to date have manipulated both of these variables while also considering theoretically important individual difference variables (e.g., political orientation). Using a criminal case simulation, this study manipulated the presence of evidence concerning mental disorders (psychopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Relatively few studies have investigated this question, but mock juror ratings of other forms of psychopathology (e.g., borderline personality traits and psychosis) do not appear to significantly predict the types of legal outcomes investigated in this meta‐analysis. These other psychological characterizations have been found to be relatively mitigating or entirely unrelated to punitive decision‐making, including perceptions of defendant guilt, death verdicts, and sentence length (Cox et al, ; Edens et al, ; Gurley & Marcus, ; Mowle et al, ). It has been argued by some (e.g., Frick & Nigg, ) that psychopathic traits are not especially more stigmatizing than other types of mental health information, but the results of this meta‐analysis in combination with findings from the individual studies noted above would seem to contradict such a claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few studies have investigated this question, but mock juror ratings of other forms of psychopathology (e.g., borderline personality traits and psychosis) do not appear to significantly predict the types of legal outcomes investigated in this meta‐analysis. These other psychological characterizations have been found to be relatively mitigating or entirely unrelated to punitive decision‐making, including perceptions of defendant guilt, death verdicts, and sentence length (Cox et al, ; Edens et al, ; Gurley & Marcus, ; Mowle et al, ). It has been argued by some (e.g., Frick & Nigg, ) that psychopathic traits are not especially more stigmatizing than other types of mental health information, but the results of this meta‐analysis in combination with findings from the individual studies noted above would seem to contradict such a claim.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of, or in addition to, summary variables based on individual item‐level ratings, four of the studies relied on singular Likert‐type ratings to assess psychopathy (e.g., Mowle, Edens, Clark, & Sörman, ), with participants instructed to globally rate how psychopathic they perceived the defendant to be after reviewing the case vignette and stimulus materials. These Likert‐type ratings included anchor points ranging from not at all psychopathic to extremely psychopathic .…”
Section: Methodsmentioning
confidence: 99%
“…Participants were also asked to what extent they believed the defendant was to blame for the incident (7-point Likert scale), whether they felt he should receive a guilty or not guilty verdict (guilty, not guilty) and, if they reported that he should be found guilty, how harshly he should be sentenced (7-point Likert scale). These questions were adapted for the purposes of the current study aims from previous mock juror research examining credibility (Henry et al 2011; Mueller-Johnson et al 2007), and blameworthiness, guilt and sentencing leniency (Mowle et al 2016; Wiley and Bottoms 2009). Following each rating participants were asked to provide qualitative responses regarding why they gave that rating (e.g., ‘Why did you give this rating of likeability?…”
Section: Methodsmentioning
confidence: 99%
“…In all study conditions, participants received the same crime vignette (104 words long; see Appendix) adopted from previous research (Mowle et al, 2016). The case described a street robbery, where a female pedestrian ("Mrs. K") was approached by a stranger ("Stenberg") who grabbed her handbag and slashed her across the face with a pocket knife.…”
Section: Crime Vignette and Fpementioning
confidence: 99%
“…Neurobiological research has demonstrated that decisions are influenced by both fast (i.e., unconscious) and slow (i.e., conscious and influenced by culture and education) aspects (Frith & Singer, 2008). Previous research has also demonstrated that political affiliation might impact legal decision-making (Mowle et al, 2016). Social and cognitive psychology is ripe with theories and evidence regarding reasoning and decision-making processes, however, the application of these theories to the study of professional judges and lay judges is lacking.…”
Section: Implications and Future Researchmentioning
confidence: 99%